Nominal Grounding Elements in English: A Domain-based Account - Fatah, Azad Hasan; Mustafa, Kobeen Raouf (Sulaimani Journal for Humanities, 2025)
The present study deals with the notion of grounding in English, using Langacker’s Cognitive Grammar framework. Grounding refers to the process of establishing an entity or event in reality. Grounding in language is of two types: nominal and clausal. Nominalgrounding, the subject-matter of the present study, involves an entity that is grounded in reality and realized by means of such grammatical elements as articles, demonstratives and quantifiers. Concerning such nominal grounding elements, the problem facing language users resides in the misuse of such elements in discourse, neglecting the semantic considerations which condition their presence. In this respect, the study hypothesizes that each nominal grounding element has its own function which distinguishes it from the others. This is done by placing the nominal grounding elements in domains, in which each grounding element represents a different facet. The aim of the study, therefore, is to present a thorough account of the nominal grounding elements in the English language. The main conclusion of the study is that nominal grounding elements gather in different domains and stand in contrast to one another when they share the same concept. Each nominal grounding element serves a different communicative purpose.